Le site du Carreau du Temple (Paris) entre “ marais ” et “ marécages ” : indices géoarchéologiques et paléo-environnementaux - Jérôme Brenot; Isabelle Caillot; Erwan Messager; Cristiano Nicosia; Aline Emery-Barbier (Revue Archéologique du Centre de la France)
The excavations of the Carreau du Temple, Paris, France, undertaken in 2011, provided the opportunity to study a pedo-sedimentary sequence preserved in the ruins of an occupation that began in the twelfth century with the development of the “Enclos du Temple”. The site is located in an area of geomorphological transition between a relief characterised by shallow ancient dunes (the “Marais”, “swamp” in French) and a paleochannel of the right bank of the river Seine. The sediment sequence, which corresponds to a homogeneous organic horizon extending across the site, was the subject of a paleo-environmental study (sedimentology, micromorphology, paleobotany) aimed at determining both its origin and evolution. The principal results found no markers indicating a wetland environment; however, extensive evidence of intensive human activity related to agricultural practices from the Middle Ages was identified, including evidence for both cereal and more specifically, vegetable production. This result agrees with the archaeological remains identified at the site and confirms the pedo-sedimentary observations made in several places along the paleo-channel, and in particular in the Marais. The absence of wetland markers that would normally indicate a marshy right river bank calls into question the toponymy of the place - the Marais - which is a name usually associated with unsanitary, swampy conditions; the evidence found, in fact indicates that this was a zone of varied agricultural production.